Direct Lyman continuum and Ly α escape observed at redshift 4. (10th February 2018) - Vanzella, E; Nonino, M; Cupani, G; Castellano, M; Sani, E; Mignoli, M; Calura, F; Meneghetti, M; Gilli, R; Comastri, A; Mercurio, A; Caminha, G B; et al.
Abstract: We report on the serendipitous discovery of a z = 4.0, M 1500 = −22.20 star-forming galaxy ( Ion3 ) showing copious Lyman continuum (LyC) leakage (∼60 per cent escaping), a remarkable multiple peaked Ly α emission, and significant Ly α radiation directly emerging at the resonance frequency. This is the highest redshift confirmed LyC emitter in which the ionizing and Ly α radiation possibly share a common ionized channel (with N H I < 10 17.2 cm −2 ). Ion3 is spatially resolved, it shows clear stellar winds signatures like the P-Cygni N v λ1240 profile, and has blue ultraviolet continuum (β = −2.5 ± 0.25, F λ ∼ λ β ) with weak low-ionization interstellar metal lines. Deep VLT/HAWKI Ks and Spitzer/IRAC 3.6 and 4.5μm imaging show a clear photometric signature of the H α line with equivalent width of 1000 Å rest-frame emerging over a flat continuum (Ks − 4.5μm ≃ 0). From the SED fitting, we derive a stellar mass of 1.5 × 10 9 M⊙, SFR of 140 M⊙ yr −1 and age of ∼10 Myr, with a low dust extinction, E ( B − V ) ≲ 0.1, placing the source in the starburst region of the SFR−M* plane. Ion3 shows similar properties of another LyC emitter previously discovered ( z = 3.21, Ion2, Vanzella et al. 2016 ). Ion3 (and Ion2 ) represents ideal high-redshift reference cases to guide the search for reionizing sources at z > 6.5 with JWST.